Identification of Privacy and Security Risks of Internet of Things: An Empirical Investigation - Hamza, Muhammad; Akbar, Muhammad Azeem; Shafiq, Muhammad; Kamal, Tahir; Baddour, Ali Mahmoud (Review of Computer Engineering Research, 2019)
The internet of things (IOT) is a phenomenon of connected devices over the internet to ease human life. It is a system where a separate computing device embedded with sensors is connected to other devices or to the cloud through the different infrastructures of the Internet. The implication of the IOT is still challenging in a geographically distributed environment. Particularly, the main challenges are associated with data privacy and security. In this study, we investigate in the report the risks/issue related to IoT data privacy and security from the existing literature for the last two years and provide a review. We identify a total of seven issues related to IoT data privacy and security. The findings revolved that Privacy, Security, confidentiality, and integrity are the most significant issues for IoT in the current era. The findings of this study provide the researchers with a body of knowledge about the critical issues faced by the users and practitioners of IOT across the globe.